The Value of Unhealthy Eating and the Ethics of Healthy Eating Policies - Barnhill, Anne (Kennedy Institute of Ethics journal, 2014)
, Unhealthy eating can have value for individuals and groups, even while it has disvalue in virtue of being unhealthy. In this paper, we discuss some ways in which unhealthy eating has value and draw out implications for the ethics of policies limiting access to unhealthy food. Discussing the value and disvalue of unhealthy eating helps identify opportunities for reducing unhealthy eating that has little value, and helps identify opportunities for eliminating trade-offs between health and other values by making unhealthy food experiences healthier without eliminating their value. It also helps us think through when it is ethically acceptable, and when it might be ethically unacceptable, to limit valuable experience in order to promote health. Our discussion of the value and disvalue of eating is offered here as a necessary supplement to the familiar discussion of paternalism, autonomous choice, and public policy.